A mixed-methods investigation of mental health stigma, absenteeism and presenteeism among UK postgraduate researchers. (10th May 2021) - Berry, Clio; Niven, Jeremy E.; Chapman, Laura A.; Valeix, Sophie; Roberts, Paul E.; Hazell, Cassie Marie
Abstract : Purpose: Postgraduate researchers (PGRs) appear to be particularly vulnerable to mental health problems. Mental health-related stigma and discrimination may be endemic within universities, creating a threatening environment that undermines PGRs' health and well-being. These environmental characteristics may increase PGRs' absenteeism and presenteeism, attendance behaviours that have great personal and institutional consequences. The study of this issue, however, has been limited to date. Design/methodology/approach: This was a mixed methods psychological study using cross-sectional data provided by 3, 352 UK-based PGRs. Data were collected in a new national survey (U-DOC) led by a British University in 2018–2019. We used structural equation modelling techniques to test associations between workplace mental health-related stigma and discrimination, presenteeism, absenteeism and demographic characteristics. The authors analysed qualitative survey data with framework analysis to deductively and inductively explore associations between workplace culture, stigma and discrimination, and attendance behaviours. Findings: The authors found that some PGRs report positive perceptions and experiences of the academic mental health-related workplace culture. However, experiences of mental health stigma and discrimination appear widespread. Both quantitative and qualitative results show that experiences of mental health-related stigma are associated with greater absenteeism and presenteeism. People with mental health problems appear especially vulnerable to experiencing stigma and its impacts. Practical implications: Key implications include recommendations for universities to improve support for PGR mental health, and to encourage taking annual leave and necessary sickness absences, by providing a more inclusive environment with enhanced mental health service provision and training for faculty and administrative staff. Originality/value: This study presents the first large-scale survey of PGR experiences of mental health-related stigma and discrimination, and their associations with absenteeism and presenteeism.